Resilience, smartphone use and language among urban refugees in the Global south. Issue 3 (17th February 2022) - Netto, Gina; Baillie, Lynne; Georgiou, Theodoros; Wan Teng, Lai; Endut, Noraida; Strani, Katerina; O'Rourke, Bernadette
ABSTRACT: The formidable challenges faced by urban refugees in the Global South have received considerable attention, calling for new approaches to support their resilience. Although critical interest in resilience and the role of digital technology in enabling refugees to navigate their new surroundings has been growing, little attention has been paid to the influence of language and literacy in processes of resilience-building and the use of such technology. This is important due to the diverse linguistic resources which refugees bring with them and the central role of language in adapting to contexts of forced displacement. We develop a conceptual framework for examining refugees' transnational use of smartphones and apply the framework to data collected from participatory workshops with fifty-four Rohingya refugees in Malaysia. Results revealed varying degrees of digital literacy, linguistic capital and literacy in three main languages: the Rohingya language which refugees bring with them, Bahasa Malaysia, the national language of Malaysia and English, which is widely spoken in Malaysia. These variations significantly shape resilience-building strategies. Greater attention to the role of language and literacy in refugees' use of digital technology will contribute to better understanding of the capacity for resilience among these individuals and more effective digital solutions.